State-society relations in the Arab Gulf States edited by Mazhar Al-Zoby and Birol Baskan - Al-Zoʻby, Mazhar; Başkan, Birol (Gerlach Press, 2014)
"This book examines the strategies and dynamics through which state-society relations in the Arab Gulf region have been cultivated, and explores the alternative political, social, economic and popular changes that threaten these relations. The work focuses on understanding how state sovereignty has been shifting to accommodate internal social, cultural, and intellectual forces and how these forces have managed to balance social and political powers in order to function within and co-exist alongside the state." --Page [4] of cover.